Efficient regeneration of styrene-saturated activated carbon: Dynamic evolution from Co0-CoMn2O4 to a defect-rich mixed interface - Yimin Wang; Jian Li; Xuning Li; Jun Liu; Xiaoqing Liu; Ying Wang; Yongfa Zhang; Guojie Zhang; Yongliang Ma; Junhua Li; Xu Wu (Journal of Environmental Chemical Engineering, 2026)

Multi-objective water–energy Co-optimization and risk-informed decision-making for hydro–wind–solar systems in arid regions - Feilin Zhu; Yaqin Wang; Weifeng Liu; Tiantian Hou; Naixi Xue; Xuning Guo; Xinyi Wang; Ping-an Zhong (Journal of Cleaner Production, 2026)

A 44-min periodic radio transient in a supernova remnant - Di Li; Mao Yuan; Lin Wu; Jingye Yan; Xuning Lv; Chaowei Tsai; Pei Wang; Jiaqi Zhao; Weiwei Zhu; Li Deng; Ailan Lan; Renxin Xu; et al. (Science Bulletin, 2026)

Microbial community structure and function and their linkages with methane production in sediments of thermokarst lakes on the Tibetan Plateau - Yutong Song; Chao Mao; Pengfei Liu; Guibiao Yang; Luyao Kang; Ziliang Li; Wei Zhou; Xuning Liu; Shiting Yao; Yuanhe Yang (Science China Life Sciences, 2026)

Complementary preservation of seafood mushroom (Hypsizygus marmoreus) by coupling low voltage electrostatic field with PBAT/PLA biodegradable packaging - Mengxuan Cao; Xuning Liu; Ruihua Bai; Jun Wang; Fengyi Liu; Fang Duan (Food Bioscience, 2026)

Analysis of the timing sequence of heat and gas generation during thermal runaway of lithium iron phosphate batteries for energy storage - Qinzheng Wang; Chenyu Zhang; Zhaoyang Liu; Hongquan Ye; Changyong Jin; Chengshan Xu; Xuning Feng; Huaibin Wang (Process Safety and Environmental Protection, 2026)

Bifunctional antifouling strategy based on polypeptide hydrogels for enhancing long-term stability of potassium ion sensors in complex systems - Wenjing Tai; Weichen Meng; Xuning Liu; Enbao Lu; Tianyu Zhang; Xiujuan Qiao; Xianghua Zeng; Zhanfeng Li; Xiliang Luo (Analytica Chimica Acta, 2026)

A hybrid process-data driven framework for real-time hydrological forecasting with interpretable deep learning - Feilin Zhu; Ou Zhu; Mingyu Han; Weifeng Liu; Xuning Guo; Tiantian Hou; Lingqi Zhao; Chengjing Xu; Ping-an Zhong (Journal of Hydrology, 2025)

Multi-step ahead probabilistic runoff forecasting with SHAP interpretability: a GPR-enhanced deep learning ensemble approach integrating teleconnection factors - Feilin Zhu; Tiantian Hou; Ou Zhu; Yitong Sun; Weifeng Liu; Lingqi Zhao; Xuning Guo; Min Li; Ping-an Zhong (Environmental Modelling & Software, 2025)

Spatio-temporal evolution and simulation prediction of heat island effect in shrinking cities in China based on improved CA-Markov modeling - Xuning Qiao; Liang Liu; Yalong Li; Yongju Yang; Yulong Dai; Jing Zhang; Jinyuan Zhang; Jinchan Zheng; Shengnan Zhao (Sustainable Cities and Society, 2025)

Virus-host interactions and their effects on the prokaryotic community in thermokarst lakes - Yutong Song; Guibiao Yang; Pandeng Wang; Xiaoqing Luo; Jian-Yu Jiao; Zhihu Zheng; Luyao Kang; Dianye Zhang; Ziliang Li; Wei Zhou; Xuning Liu; Lili Han; et al. (Science Bulletin, 2025)

Explosion limits of binary mixtures of ammonia and additives (hydrogen, natural gas, and diethyl ether) - Qiang Guo; Jie Liu; Lu Zhang; Xuning Feng; Hewu Wang (Fuel, 2025)

Enhanced barrier materials with integrated gas regulation capabilities to mitigate explosion risks in battery systems - Jingyu Chen; Chengshan Xu; Junyuan Liu; Ye Sun; Shaw Kang WONG; Wenyu Dong; Hongni Huang; Zhikai Yang; Yong Peng; Jiangyun Zhang; Languang Lu; Guoqing Zhang; et al. (Chemical Engineering Journal, 2025)

The influence of climate and human factors on a regional heat island in the Zhengzhou metropolitan area, China - Xuning Qiao; Yalong Li; Yu Wang; Liang Liu; Shengnan Zhao (Environmental Research, 2024)

Patterns and drivers of prokaryotic communities in thermokarst lake water across Northern Hemisphere - Luyao Kang; Leiyi Chen; Ziliang Li; Jianjun Wang; Kai Xue; Ye Deng; Manuel Delgado‐Baquerizo; Yutong Song; Dianye Zhang; Guibiao Yang; Wei Zhou; Xuning Liu; et al. (Global Ecology and Biogeography, 2023)
Aim The formation of thermokarst lakes could make a large amount of carbon accessible to microbial degradation, potentially intensifying the permafrost carbon‐climate feedback via carbon dioxide/methane emissions. Because of their diverse functional roles, prokaryotes could strongly mediate biogeochemical cycles in thermokarst lakes. However, little is known about the large‐scale patterns and drivers of these communities. Location Permafrost regions in the Northern Hemisphere. Time period Present day. Major taxa studied Prokaryotes. Methods Based on a combination of large‐scale measurements on the Tibetan Plateau and data syntheses in pan‐Arctic regions, we constructed a comprehensive dataset of 16S rRNA sequences from 258 thermokarst lakes across Northern Hemisphere permafrost regions. We also used the local contributions to beta diversity (LCBD) to characterize the variance of prokaryotic species composition and screened underlying drivers by conducting a random forest modelling analysis. Results Prokaryotes in thermokarst lake water were dominated by the orders Burkholderiales, Micrococcales, Flavobacteriales and Frankiales. The relative abundance of dominant taxa was positively associated with dissolved organic matter (DOM) properties, especially for the chromophoric/aromatic compounds. Microbial structure differed between high‐altitude and high‐latitude thermokarst lakes, with the dominance of Flavobacterium in high‐altitude lakes, and the enrichment of Polynucleobacter in high‐latitude lakes. More importantly, climatic variables were among the main drivers shaping the large‐scale variation of prokaryotic communities. Specifically, mean annual precipitation was the best predictor for prokaryotic beta diversity across the Northern Hemisphere, as well as in the high‐altitude permafrost regions, while mean annual air temperature played a key role in the high‐latitude thermokarst lakes. Main conclusions Our findings demonstrate significant associations between dominant taxa and DOM properties, as well as the important role of climatic factors in affecting prokaryotic communities. These findings suggest that climatic change may alter DOM conditions and induce dynamics in prokaryotic communities of thermokarst lake water in the Northern Hemisphere.

Accelerated organic matter decomposition in thermokarst lakes upon carbon and phosphorus inputs - Ziliang Li; Weijie Xu; Luyao Kang; Yakov Kuzyakov; Leiyi Chen; Mei He; Futing Liu; Dianye Zhang; Wei Zhou; Xuning Liu; Yuanhe Yang (Global Change Biology, 2023)
Mineralization of dissolved organic matter (DOM) in thermokarst lakes plays a non‐negligible role in the permafrost carbon (C) cycle, but remains poorly understood due to its complex interactions with external C and nutrient inputs (i.e., aquatic priming and nutrient effects). Based on large‐scale lake sampling and laboratory incubations, in combination with 13 C‐stable‐isotope labeling, optical spectroscopy, and high‐throughput sequencing, we examined large‐scale patterns and dominant drivers of priming and nutrient effects of DOM biodegradation across 30 thermokarst lakes along a 1100‐km transect on the Tibetan Plateau. We observed that labile C and phosphorus (P) rather than nitrogen (N) inputs stimulated DOM biodegradation, with the priming and P effects being 172% and 451% over unamended control, respectively. We also detected significant interactive effects of labile C and nutrient supply on DOM biodegradation, with the combined labile C and nutrient additions inducing stronger microbial mineralization than C or nutrient treatment alone, illustrating that microbial activity in alpine thermokarst lakes is co‐limited by both C and nutrients. We further found that the aquatic priming was mainly driven by DOM quality, with the priming intensity increasing with DOM recalcitrance, reflecting the limitation of external C as energy sources for microbial activity. Greater priming intensity was also associated with higher community‐level ribosomal RNA gene operon ( rrn ) copy number and bacterial diversity as well as increased background soluble reactive P concentration. In contrast, the P effect decreased with DOM recalcitrance as well as with background soluble reactive P and ammonium concentrations, revealing the declining importance of P availability in mediating DOM biodegradation with enhanced C limitation but reduced nutrient limitation. Overall, the stimulation of external C and P inputs on DOM biodegradation in thermokarst lakes would amplify C‐climate feedback in this alpine permafrost region.

Patterns and drivers of anaerobic nitrogen transformations in sediments of thermokarst lakes - Chao Mao; Yutong Song; Yunfeng Peng; Luyao Kang; Ziliang Li; Wei Zhou; Xuning Liu; Futing Liu; Guibing Zhu; Yuanhe Yang (Global Change Biology, 2023)
Significant attention has been given to the way in which the soil nitrogen (N) cycle responds to permafrost thaw in recent years, yet little is known about anaerobic N transformations in thermokarst lakes, which account for more than one‐third of thermokarst landforms across permafrost regions. Based on the N isotope dilution and tracing technique, combined with qPCR and high‐throughput sequencing, we presented large‐scale measurements of anaerobic N transformations of sediments across 30 thermokarst lakes over the Tibetan alpine permafrost region. Our results showed that gross N mineralization, ammonium immobilization, and dissimilatory nitrate reduction rates in thermokarst lakes were higher in the eastern part of our study area than in the west. Denitrification dominated in the dissimilatory nitrate reduction processes, being two and one orders of magnitude higher than anaerobic ammonium oxidation (anammox) and dissimilatory nitrate reduction to ammonium (DNRA), respectively. The abundances of the dissimilatory nitrate reduction genes ( nirK , nirS , hzsB , and nrfA ) exhibited patterns consistent with sediment N transformation rates, while α diversity did not. The inter‐lake variability in gross N mineralization and ammonium immobilization was dominantly driven by microbial biomass, while the variability in anammox and DNRA was driven by substrate supply and organic carbon content, respectively. Denitrification was jointly affected by nirS abundance and organic carbon content. Overall, the patterns and drivers of anaerobic N transformation rates detected in this study provide a new perspective on potential N release, retention, and removal upon the formation and development of thermokarst lakes.

Urban Expansion in Major Grain Producing Area from 1978 to 2017: A Case Study of Zhengzhou Metropolitan Area, China - Yongju Yang; Hebing Zhang; Xuning Qiao; Liang Liu; Jinchan Zheng (Chinese Geographical Science, 2023)